Experimental evidence of the role of heterochrony in evolution of the Mesoamerican cichlids pigment patterns. Issue 1 (21st September 2018) - Prazdnikov, Denis V.; Shkil, Fedor N.
Abstract : The Mesoamerican cichlids display a spectacular diversity of pigment patterns, which serve a variety of functions and serve as a strong selective trait for this lineage. The development and variation of coloration in the Mesoamerican cichlids have been detailed by several groups. In particular, Říčan, Musilová, Muška, and Novák (2005 ) and Říčan, Piálek, Dragová, and Novák (2016 ) determined homology of pattern and revealed four alternative types of coloration and their ontogeny. In this work, this group posed an "ontogenetic timing hypothesis" proposing heterochronic shifts underlying major transitions in the evolution of the Mesoamerican cichlids. Here, we experimentally test this hypothesis by experimentally altering timing of pigment pattern formation in the convict cichlid Amatitlania nigrofasciata, a member of the Mesoamerican cichlids, via manipulations of thyroid hormone (TH) function. The response of different pigment cell lineages to TH‐perturbations revealed that the transition from larval to juvenile coloration in the convict cichlid is under the control of TH‐signaling. Importantly, hormonally induced changes in the timing of pigment cell lineages' development resulted in shifts of coloration ontogeny type observed between lineages and led to the appearance of phenotypes mimicking those in phylogenetically close and distant species. Thus, our findings support the hypothesis that simple changes in ontogenetic timing underlies species specific patterns in pigmentation and provide new perspectives for studying the role of endocrine signaling in the evolution of cichlids.